Eucalyptus Globulus in Homoeopathy: Traditional Wisdom Meets Modern Healing with Acute Case Study (Homoeopathy for All, 2025)
In the ancient time Eucalyptus globulus used for the various purpose. It is a tall and an evergreen tree that can grow up to the height of 70m and its diameter is about 4 to7ft. which was first found on the island of Tasmania in 1792 which associate to the Myrtaceous family which is commonly called as Tasmanian Blue Gum, southern blue gum or blue gum are the different names of eucalyptus globulus grow in the various parts of India. The particular species of Eucalyptus globulus have been used for various purposes. It had been found that eucalyptus is a rich source of phytochemical constituent and also possesses medicinal use. Phytochemical analysis of this plant has revealed that Mother tincture extracted from leaf contain 1,8-cineole, α-pinene, p-cymene, cryptone and spathulenol. Due to these chemical compounds, Eucalyptus glabrous is found to be a potential anti-microbial, anti fungal, anti-viral, anti-inflammatory, analgesic, anti-nociceptive and anti-oxidant agent of nature. Some recent scientific investigations have also revealed that essential oil of Eucalyptus globusus also have anti diabatic potentials that enhances its market value due to excessive usage in number of pharmaceutical products of traditional and advanced system of medicines.[1,2,3] The aim of this review paper is compiling all the information about Eucalyptus Globulus such as Decongestant, Anti-pyretic, Anti-inflammatory, Analgesic, Anti-nociceptive, Antimicrobial, Anti-fungal, Anti viral and Anti-oxidant agent of the nature with Acute Case Records & So that which can be used effectively in Treatment of Patients of Acute Viral Conditions like URTI, Influenza, Covid-19, Common Cold etc.
Keywords: Eucalyptus globulus; Anti-inflammatory; Antipyretics; Decongestant; Review Article